1996
DOI: 10.1175/1520-0477(1996)077<0693:aosotd>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

An observational Study of the “Interstate 5” Dust Storm Case

Abstract: On 29 November 1991 a series of collisions involving 164 vehicles occurred on Interstate 5 in the San Joaquin Valley in California in a dust storm that reduced the visibility to near zero. The accompanying high surface winds are hypothesized to result from intense upper-tropospheric downward motion that led to the formation of a strong upper front and tropopause fold and that transported high momentum air downward to midlevels where boundary layer processes could then mix it to the surface. The objectives of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
71
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(72 citation statements)
references
References 7 publications
(15 reference statements)
1
71
0
Order By: Relevance
“…More information on density currents can be found in Knippertz et al (2007), Emmel et al (2010), Knippertz and Todd (2012). Pauley et al (1996) described a dust storm on 29 November 1991 that caused a pileup on Interstate 5 in California, US, involving 164 vehicles. They reported that dust uptake came from surrounding agricultural areas that were left unplanted after being plowed, before the rainy season began; disturbing a soil surface makes it more susceptible to dust generation (Gillete et al, 1980).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…More information on density currents can be found in Knippertz et al (2007), Emmel et al (2010), Knippertz and Todd (2012). Pauley et al (1996) described a dust storm on 29 November 1991 that caused a pileup on Interstate 5 in California, US, involving 164 vehicles. They reported that dust uptake came from surrounding agricultural areas that were left unplanted after being plowed, before the rainy season began; disturbing a soil surface makes it more susceptible to dust generation (Gillete et al, 1980).…”
Section: Introductionmentioning
confidence: 99%
“…They reported that dust uptake came from surrounding agricultural areas that were left unplanted after being plowed, before the rainy season began; disturbing a soil surface makes it more susceptible to dust generation (Gillete et al, 1980). Pauley et al (1996) also noted that in these agricultural regions dust is present often enough that the US Environmental Protection Agency (EPA) is proposing sanctions for San Joaquin Valley growers for not attending the standard for PM 10 (particulate matter of 10 micrometers or less). It should also be noted that drought conditions had prevailed in that area for 6 years.…”
Section: Introductionmentioning
confidence: 99%
“…Dust storms potentially reduce the visibility to zero and cause dramatic pile-ups. These phenomena are likely to occur in dry agricultural areas subject to land erosion, like the I-5 in California's San Joaquin Valley in 1991 (164 vehicles involved, 151 injured, 17 dead) (Pauley et al, 1996) or the A19 Mecklenburg-Vorpommern in Germany in 2011 (82 vehicles involved, 100 injured, 8 dead) (Hunfeld et al, 2011). Smoke caused by factories or fires in the vicinity of highways is also a dramatic source of reduction of the visibility (AbdelAty et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, there have been parallel studies outside of China on this subject. Examples include: Chung et al (2003), who studied dust storms and associated dust fall observed in Chongju-Chongwon, Korea, during 1997Korea, during -2000Lee et al (2003), who studied the long-range transport of Asian dust from dust storms and its impact on Japan; McTainsh et al (1998), who made an analysis of the effects from climatic changes on dust storms in the dry and semi-dry regions of Australia; and Pauley et al (1996), who diagnosed and analysed five dust storm events in the San Joaquin valley, California, USA.…”
Section: Introductionmentioning
confidence: 99%